2014 4th International Conference on Wireless Communications, Vehicular Technology, Information Theory and Aerospace &Amp; Elec 2014
DOI: 10.1109/vitae.2014.6934442
|View full text |Cite
|
Sign up to set email alerts
|

Constructions of optimal and almost optimal locally repairable codes

Abstract: Constructions of optimal locally repairable codes (LRCs) in the case of (r + 1) n and over small finite fields were stated as open problems for LRCs in [I. Tamo et al., "Optimal locally repairable codes and connections to matroid theory", 2013 IEEE ISIT]. In this paper, these problems are studied by constructing almost optimal linear LRCs, which are proven to be optimal for certain parameters, including cases for which (r + 1) n. More precisely, linear codes for given length, dimension, and all-symbol locality… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In the last section, we saw that the p-c matrix of a rate-optimal seq-LRC can be assumed without loss of generality, to have the staircase form appearing in equations (11) and (12). It will be shown in the present section, just as was done in the case of the examples presented in Section III, that this form of p-c matrix leads to a graphical representation of the code.…”
Section: A Graphical Representation For the Rate-optimal Seq-lrcmentioning
confidence: 92%
See 2 more Smart Citations
“…In the last section, we saw that the p-c matrix of a rate-optimal seq-LRC can be assumed without loss of generality, to have the staircase form appearing in equations (11) and (12). It will be shown in the present section, just as was done in the case of the examples presented in Section III, that this form of p-c matrix leads to a graphical representation of the code.…”
Section: A Graphical Representation For the Rate-optimal Seq-lrcmentioning
confidence: 92%
“…Also contained in [10] is a construction of codes with all-symbol locality having field size of O(n) whose minimum distance differs by at most 1 from the bound given in (1) when r k, n = 1 (mod r + 1). In [11], the authors show that codes with all-symbol locality whose minimum distance differs by atmost 1 from the bound given in (1) can be constructed for any n, k, r. However the construction provided in [11] has field size exponential in n.…”
Section: A Background On Single-erasure Lrcmentioning
confidence: 99%
See 1 more Smart Citation
“…5) It is shown in [103] that one can construct codes with AS locality and field size of order n whose minimum distance is within 1 of the bound in (18) provided r k, n = 1 (mod r + 1). In [104], it is shown that this can be achieved for any parameter set if one permits the field size to be exponential in n.…”
Section: ) the Pyramid-code Construction In Vii-b1 Provides A Generamentioning
confidence: 99%
“…In this last construction the field size has to be at least the length of the code. In addition to the constructions mentioned above there are several other constructions of LRCs, see e.g., [4], [7]- [9], [12], [19].…”
Section: Introductionmentioning
confidence: 99%